2016
DOI: 10.1128/aac.02853-15
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Experience with Primary Oral Medical Therapy for Mycobacterium ulcerans Disease in an Australian Cohort

Abstract: c Buruli ulcer (BU) is a necrotizing infection of subcutaneous tissue that is caused by Mycobacterium ulcerans and is responsible for disfiguring skin lesions. The disease is endemic to specific geographic regions in the state of Victoria in southeastern Australia. Growing evidence of the effectiveness of antibiotic therapy for M. ulcerans disease has evolved our practice to the use of primarily oral medical therapy. An observational cohort study was performed on all confirmed M. ulcerans cases treated with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 17 publications
0
55
0
Order By: Relevance
“…The remaining child, a 17‐month‐old male, was initially treated with 56 days of oral antibiotic therapy (rifampicin and clarithromycin), although he experienced culture positive disease recurrence 4 months later. Retreatment with the same oral antibiotic regimen and duration was successful and the lesion healed by secondary intention 16 months after commencement of initial therapy …”
Section: Resultsmentioning
confidence: 98%
“…The remaining child, a 17‐month‐old male, was initially treated with 56 days of oral antibiotic therapy (rifampicin and clarithromycin), although he experienced culture positive disease recurrence 4 months later. Retreatment with the same oral antibiotic regimen and duration was successful and the lesion healed by secondary intention 16 months after commencement of initial therapy …”
Section: Resultsmentioning
confidence: 98%
“…In this study, we have shown that despite its known effectiveness, there is a significant toxicity associated with the antibiotic treatment of M . ulcerans in an Australian population.…”
Section: Discussionmentioning
confidence: 78%
“…In this study, we have shown that despite its known effectiveness, 7,8 there is a significant toxicity associated with the antibiotic treatment of M. ulcerans in an Australian population. More than one in five patients experienced an adverse effect severe enough to warrant cessation of an antibiotic, and a significant number required hospitalisation to manage their toxicity.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…[13] Circumstantial evidence from observational studies suggests that fully oral treatment is highly e ective. [14] [15] The Cochrane Review is the first of its kind to formally assess the available evidence for drug treatment of Buruli ulcer. [4] The advantage of this formal evaluation of all peer-reviewed, published literature is that the many flaws in methodology are highlighted and suggestions for future trials are made.…”
mentioning
confidence: 99%